When our eyes no longer see : realism, science, and ecology in Japanese literary modernism - Golley, Gregory, 1964- (Cambridge, Mass. : Published by the Harvard University Asia Center : Distributed by Harvard University Press, 2008)
As industrial and scientific developments in early-twentieth-century Japan transformed the meaning of "objective observation," modern writers and poets struggled to capture what they had come to see as an evolving network of invisible relations joining people to the larger material universe. For these artists, literary modernism was a crisis of perception before it was a crisis of representation. When Our Eyes No Longer See portrays an extraordinary moment in the history of this perceptual crisis and in Japanese literature during the 1920s and 1930s. The displacement in science of "positivist" notions of observation by a "realist" model of knowledge provided endless inspiration for Japanese writers. Gregory Golley turns a critical eye to the ideological and ecological incarnations of scientific realism in several modernist works: the photographic obsessions of Tanizaki Jun'ichiro's Naomi, the disjunctive portraits of the imperial economy in Yokomitsu Riichi's Shanghai, the tender depictions of astrophysical phenomena and human-wildlife relations in the children's stories of Miyazawa Kenji. Attending closely to the political and ethical consequences of this realist turn, this study focuses on the common struggle of science and art to reclaim the invisible as an object of representation and belief.
The Revolt against Positivism -- Science and Sensibility -- Art and Accuracy -- Language and the Politics of Realism -- The Things of This World -- Part I Art, Empire - 1. Erotic Science: Realism and Aesthetics in the Fiction of Tanizaki Jun'ichiro -- Surface and Depth -- Pornographic Realism -- Truth in Advertising -- Erotic Science - 2. A Dark Ecology: Yokomitsu Riichi's Universe -- When Was Shanghai? -- A Dark Ecology -- Mapping the Empire -- The Fourth Person -- Part II Earth, Stars - 3. Things Near and Far Away: Geometry and Ethics in the Stories of Miyazawa Kenji -- You Are Here -- Society and the Fourth Dimension -- Space Is Not Empty -- The Ethics of Realism - 4. The Wild and the Cultivated: Kenji, Darwin, and the Rights of Nature -- The Wild and the Cultivated -- The Sacramental Economy -- The Border Country -- Progress and the Struggle for Existence - 5. Brethren in Pain: Beauty, Objectivity, and the Lives of Bears -- The Accurate and the Beautiful -- Love and Objectivity.
Includes bibliographical references and index.
Keywords: Japanese literature -- 20th century -- History and criticism; Modernism (Literature) -- Japan